Next generation security operation center framework - Mohamad Fadli, Zolkipli; Yau, Alan Ti Dun; Azizah, Abdul Aziz; Bee, Tan Fui (2018)
Security Operation Centers (SOC) area necessary monitoring security solution for organization who want to have visibility on cybersecurity assets.